Effect of Pravastatin on Biomolecular Parameters of Preeclampsia in the Placenta of Wistar Rats - Bambang Rahardjo, Fauqo Wildatil Jannah, Anita Dwi Rahmawati, Kunawati Tungga Dewi, Agustina Tri Endharti, Sutrisno, Anin Andriani (Pakistan Journal of Medical & Health Sciences, 2022)
The etiology of preeclampsia consists of 2 stages, first, abnormal placentation which can increase ROS, and the inflammatory response then progresses to angiogenic imbalance. Pravastatin has a pleiotropic effect that can act as an antioxidant, anti-inflammatory, and anti-apoptotic, which is expected to be a vasodilator for angiogenic balance and reduce proinflammatory cytokines. This study aimed to examine the effect of pravastatin on the expression of angiogenic factors (sFlt-1 and VEGF) and inflammatory response (TNF-α and IL-10) in the placenta of preeclamptic rat models. This study is an experimental study, only post- test with a control group design using the placenta of preeclamptic rat models (L-NAME induced) and given pravastatin in 3 doses, namely 2 mg, 4 mg, and 8 mg. The One Way Anova test results on sFlt-1 and VEGF expressions showed p-value 0.000<α and TNF-α and IL-10 expressions had p-value 0.000<α. Based on the results of the correlation test, the value of pravastatin dose on sFLT-1 expression was strongly related (r=-0.871, p-value 0.000<α); VEGF is strongly related (r= 0.863. p-value < α); TNF-α is strongly related (r=-.839, p-value 0.000<α) and IL-10 is moderately related (r= 0.682, p-value<α). In conclusion, pravastatin can increase VEGF and IL-10 expression and decrease sFlt-1 and TNFα expression.